Effect of pre-lambing supplementation on milk production of Merino ewes at grazing - Gallego, F L; Parra, M L; Sanchez, F P (MILKING AND MILK PRODUCTION OF DAIRY SHEEP AND GOATS, 1999)
Milk production of Merino ewes has been studied under the effects of two different prelambing supplementations (4 and 7 weeks, L1 and L2, respectively). Throughout the trial, the ewes remained under extensive grazing in a ``dehesa{''} from Extremadura. Lambing took place in September and lactation continued until the 6(th) week. After weaning, the ewes were subjected to machine milking until drying in the 19(th) week. During milking, the ration for both lots was the same. Similar daily values of production potential were noted, being greater in L2, 12% during lactation (1120ml) and 14% in milking (375ml). The milk obtained by the lamb at 42 days of lactation (40 l) was 11% superior in lot 2. The difference in body condition is balanced out during the 90 days of milking during which the milk production obtained in L2 (27 l) represents a 16% improvement in production.
Keywords: grazing and supplementation; Merino; milk production

Effect of pre-lambing supplementation on milk production of Merino ewes at grazing - Gallego, F. L.; Parra, M. L.; Sanchez, F. P. (MILKING AND MILK PRODUCTION OF DAIRY SHEEP AND GOATS, 1999)
Milk production of Merino ewes has been studied under the effects of two different prelambing supplementations (4 and 7 weeks, L1 and L2, respectively). Throughout the trial, the ewes remained under extensive grazing in a ``dehesa{''} from Extremadura. Lambing took place in September and lactation continued until the 6(th) week. After weaning, the ewes were subjected to machine milking until drying in the 19(th) week. During milking, the ration for both lots was the same. Similar daily values of production potential were noted, being greater in L2, 12% during lactation (1120ml) and 14% in milking (375ml). The milk obtained by the lamb at 42 days of lactation (40 l) was 11% superior in lot 2. The difference in body condition is balanced out during the 90 days of milking during which the milk production obtained in L2 (27 l) represents a 16% improvement in production.
The following values have no corresponding Zotero field: periodical: MILKING AND MILK PRODUCTION OF DAIRY SHEEP AND GOATS issue: 95 pub-location: POSTBUS 220, 6700 AE WAGENINGEN, NETHERLANDS
Keywords: grazing and supplementation; Merino; milk production